Innate immune TLR7 signaling mediates platelet activation and platelet-leukocyte aggregate formation in murine bacterial sepsis - Brittney Williams; Jing Zhu; Lin Zou; Wei Chao (Platelets, 2022)
Thrombocytopenia is a common complication in sepsis and is associated with higher mortality. Activated platelets express CD62P, which facilitates platelet-leukocyte aggregate (PLA) formation and contributes to thrombocytopenia in sepsis. We have reported that thrombocytopenia in murine sepsis is partly attributable to TLR7 signaling, but the underlying mechanism is unclear. In the current study, we tested the hypothesis that TLR7 mediates platelet activation and PLA formation during sepsis. In vitro, whole blood from WT mice treated with loxoribine, a TLR7 agonist, exhibited a dose-dependent increase in activated platelets compared to the control (PBS with 0.05% DMSO) or loxoribine-treated TLR7−/− whole blood. In a murine model of sepsis, there was a significant increase in platelet activation and PLA formation 24 hours after cecal ligation and puncture (CLP) as evidenced by double positive expression of CD41+/CD62P+ and CD45+/CD62P+, respectively. The sepsis-induced PLA formation was significantly attenuated in TLR7−/− mice. Finally, in ex-vivo experiments, plasma isolated from septic mice induced WT platelet activation, but such effect was significantly attenuated in platelets deficient of TLR7. These findings demonstrate a pivotal role of TLR7 signaling in platelet activation and PLA formation during bacterial sepsis.